The Use of Figurative Language in Adel Tawil's Song Lyrics from the Album So schön anders - Zira Adira Surya Putri; Fauzan Adhima; Muhammad Nur Ashar Asnur (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2026)
Song lyrics are a way for songwriters to share their feelings, experiences, and messages. To do this indirectly, they often use figurative language to make the emotions deeper. This study aims to identify the types of figurative language used in Adel Tawil’s songs and explain what they mean. The research uses a descriptive qualitative method, focusing on three songs: Ist da jemand, Mein Leben ohne mich, and So schön anders. The data were collected by listening to the songs and taking notes, then analyzed using the Miles and Huberman model. The results show four types of figurative language: metaphor, symbol, personification, and comparison. Metaphor is the most used (21 data), followed by symbols and comparisons (3 data each), and personification (1 data). This shows that Adel Tawil likes to use metaphors to turn abstract feelings into concrete words so they are easier for listeners to understand. This study is expected to help in literary analysis and German language learning.